2017
DOI: 10.1113/jp274336
|View full text |Cite
|
Sign up to set email alerts
|

Role of nerve–muscle interactions and reactive oxygen species in regulation of muscle proteostasis with ageing

Abstract: Skeletal muscle ageing is characterised by atrophy, a deficit in specific force generation, increased susceptibility to injury, and incomplete recovery after severe damage. The hypothesis that increased generation of reactive oxygen species (ROS) in vivo plays a key role in the ageing process has been extensively studied, but remains controversial. Skeletal muscle generates ROS at rest and during exercise. ROS can cause oxidative damage particularly to proteins. Indeed, products of oxidative damage accumulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 56 publications
1
26
0
1
Order By: Relevance
“…Sod1 KO mice reveal a number of phenotypes that mimic features of sarcopenia in old wild‐type (WT) mice, including loss of innervation, mitochondrial dysfunction, and increased generation of mitochondrial ROS (mtROS) . We have also shown that loss of innervation is associated with increased mtROS and downstream activation of muscle atrophy and weakness . In this study, we asked whether increased skeletal muscle mtROS induced by skeletal muscle‐specific deletion of the mitochondrial form of SOD (MnSOD), independent of loss of innervation, is sufficient to induce muscle atrophy and weakness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sod1 KO mice reveal a number of phenotypes that mimic features of sarcopenia in old wild‐type (WT) mice, including loss of innervation, mitochondrial dysfunction, and increased generation of mitochondrial ROS (mtROS) . We have also shown that loss of innervation is associated with increased mtROS and downstream activation of muscle atrophy and weakness . In this study, we asked whether increased skeletal muscle mtROS induced by skeletal muscle‐specific deletion of the mitochondrial form of SOD (MnSOD), independent of loss of innervation, is sufficient to induce muscle atrophy and weakness.…”
Section: Introductionmentioning
confidence: 99%
“…2,[11][12][13] We have also shown that loss of innervation is associated with increased mtROS and downstream activation of muscle atrophy and weakness. 4,11,14 In this study, we asked whether increased skeletal muscle mtROS induced by skeletal muscle-specific deletion of the mitochondrial form of SOD (MnSOD), independent of loss of innervation, is sufficient to induce muscle atrophy and weakness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a denervated fibre will immediately begin to atrophy, but will survive for an ill-defined amount of time, and these have been observed in a number of human biopsies ( Lexell and Taylor, 1991 ; Spendiff et al, 2016 ; Zampieri et al, 2015 ). Further associations of age-related denervation and impaired reinnervation have been established in animal models, including alterations in oxidative stress ( Jackson and Mcardle, 2016 ; Vasilaki et al, 2017 ), dysregulation of sterol metabolism in the nervous system ( Pannérec et al, 2016 ), conversion of voltage-gated sodium channels on fibre membranes ( Rowan et al, 2012 ) and a reduction in the number of key maintenance proteins such as PGC1-a ( Gouspillou et al, 2013 ). As previously mentioned the number of SCs is decreased with age ( Verdijk et al, 2014 ), and their involvement extends beyond the maintenance of the fibre; acting as a source of post-synaptic myonuclei their reduction results in reduced maintenance of this region and ultimately degeneration of the NMJ ( Liu et al, 2017 ), and poor fibre regeneration following reinnervation ( Dedkov et al, 2001 ).…”
Section: Muscle Fibre Loss In Humans: Quantification Evidence and Mementioning
confidence: 99%
“…Insulin resistance will invariably impact muscle mass and function through an imbalance between protein synthesis and degradation (Hebert & Nair, ). Moreover, in ageing rodent studies, increases in ROS have been associated with accumulation of oxidized proteins and altered proteostasis, leading to denervation of motor units, and consequently, loss of muscle innervation, muscle fibre atrophy and loss of muscle function (discussed in more detail in Vasilaki et al., ). Opening of the mPTP plays an important role in the regulation of programmed cell death, and hence muscle fibre degeneration (i.e.…”
Section: Type 1 Diabetes: Impact On Skeletal Muscle and Mitochondriamentioning
confidence: 99%